A Rare Case of Organized Spinal Chronic Subdural Hematoma Associated with Unknown Fever (Nepal Journal of Neuroscience, 2025)
Background: Non-traumatic spinal subdural hematoma is a rare condition that may present as a chronic subdural hematoma in rare instances and subsequently progress to an organized form. Here, we report the case of a 68-year-old woman with a history of atrial fibrillation who was receiving non-vitamin K antagonist oral anticoagulant therapy.Case Description: The patient presented with sudden-onset left-sided hemiparesis and was transferred to a local hospital. There was no evidence of ischaemic stroke on brain magnetic resonance imaging (MRI); however, intravenous tissue plasminogen activator therapy was initiated 1 h 30 min after symptom onset. The patient’s symptoms persisted despite the treatment. Subsequently, she developed persistent high-grade fever (>39°C) of unknown origin despite extensive investigations and empirical antibiotic therapy. Spinal MRI revealed an intradural lesion compressing the spinal cord at the C6–T2 level on day 22, which was a suspected spinal subdural abscess. Consequently, she was referred to our hospital, where imaging findings led to the diagnosis of a subdural hematoma. Conservative management was initially commenced; however, the persistent unexplained fever and absent neurological improvement necessitated surgical intervention on day 57. Intraoperatively, we observed thickened arachnoid membranes and organized yellowish hematomas in the subdural space, confirming the diagnosis of organized spinal chronic subdural hematoma. Postoperatively, the left-sided hemiparesis gradually improved. Therefore, she was transferred for rehabilitation 21 days post-surgery.Conclusion: In this case report, we highlighted spinal subdural hematomas, which are rare and occasionally progress to an organized chronic form. Surgical treatment is crucial to reverse neurological deficits.